2013
DOI: 10.1177/1524839913507578
|View full text |Cite
|
Sign up to set email alerts
|

Experience Preferred

Abstract: Universities offering undergraduate degrees in health promotion or health education and/or graduate degrees in public health typically require an internship, practicum, or fieldwork experience. This type of mentored experience is an important aspect of career development for the next generation of public health professionals and benefits not only the students but also the profession and the communities in which they work. This article provides perspectives from four public health professionals who have recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Practical placements are extremely beneficial to students, 10 17 as evidenced by their integration into many of the leading public health masters' programmes worldwide. However, this review demonstrated significant variation in practicum design, use of guidelines, and accreditation between the programmes reviewed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Practical placements are extremely beneficial to students, 10 17 as evidenced by their integration into many of the leading public health masters' programmes worldwide. However, this review demonstrated significant variation in practicum design, use of guidelines, and accreditation between the programmes reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…These mentored experiences are also critical to career development, providing unique opportunities to develop professional networks, gain experience in different work-environments and collaborate with others in the field of public health. 10 This model builds on the traditional research-focused thesis paradigm towards one of implementation science, where the new generation of public health practitioners are supported to develop interdisciplinary skills for multisector engagement to move from research to action. 9 11 …”
Section: Introductionmentioning
confidence: 99%
“…Early-career public health professionals indicate that experiences in practice are essential to acquiring needed skills and developing mentors and role models ( 13 , 24 ). The presentation of products generated by practice-based courses and the delivery of services though service-learning experiences can also strengthen academic–practice relationships and improve training of the next generation of the public health workforce by establishing connections in the field.…”
Section: Recruit Train Sustainmentioning
confidence: 99%
“…Without adequate practical exposure during training, students are vulnerable to developing an inability to apply classroom knowledge to real world problems. Studies show that practicums and internships allow students to exercise the learned competencies on actual public health challenges and to develop lasting professional networks (14)(15)(16). Above all, providing in-training experiential exposure helps students focus on the outcomes of their education in terms of developing relevant competencies (17).…”
Section: Area Of Inquiry 2: Knowledge and Skill Sets That The Fresh Gmentioning
confidence: 99%